Cultural Curating and the Practices of Light: Speculating Diffractively. (April 2016) - Dziekan, Vince
Abstract: Drawing inspiration from New Materialist philosopher Karen Barad's challenge to read "diffractively" by experimenting with different patterns of relationality, this article sets out a course of speculative inquiry inspired by the contemporary fascination with digital light‐based installations. Taking the UN's designation of 2015 as the "International Year of Light and Light‐based Technologies" as its point of departure, a subset of mediated environments are identified that transcend the distinction between physical and digital; materiality and immateriality; invisibility and presence. Employing new technologies to create deeply sensorial and highly participatory forms of aesthetic engagement, the selected examples offer a compelling indication of the post‐digital aesthetics that arise from the interrelationship of art, design and computation. Its investigation is structured as a montage of two parts: following an introduction that surveys an illustrative sub‐set of contemporary digital light‐based art works drawn from the 2014 INST‐INT conference, the second half of this text will speculate upon the "dynamic‐constructive" relationship between digital media and the form‐making processes associated with "practices of light" (Cubitt2014 ). The implications of "post‐screen media" for curatorial practice is explored in relation to the mediating function played by modes of exhibition and other program architectures.